SOCIO-ECONOMIC ESSENCE OF COMPETITIVENESS OF THE WORKING POPULATION - Stozhok, Liudmyla (Сталий розвиток економіки, 2023)
Purpose. Investigation of the essence of the competitiveness of the working population as a socio-economic category in order to ensure the implementation of constitutionally guaranteed rights and guarantees throughout life. Methodology of research. To achieve the goal, the following general scientific methods of research are used: dialectics and scientific abstraction – in studying the content of the category of competitiveness in the labour market; analysis and synthesis – when disclosing the essence of social insurance in recreating the human capital of the working population; systematic and structural analysis – in the disclosure of scientific approaches to determining the competitiveness of the working population as a socio-economic category; analytical and monographic – in the development of literary, statistical and Internet sources; abstract and logical – for the generalization of the above material and the formulation of conclusions. Findings. It is substantiated that the accumulation of human capital takes place throughout life, and use – during labour activities in the system of social and labour relations with a view to realization of social rights and guarantees. It is proved that one of mechanisms of accumulation, reproduction and preservation of human capital is the presence of a well-established system of social protection of the worker population from social risks. It has been discovered that the competitiveness of the labour force involves the accumulation, preservation and enhancement of properties that create competitive advantages, the realization of which ensures the formation of the necessary material security, the level and quality of life. It is proved that the basis for forming the competitiveness of working population is the demographic, educational qualification, professional and socio-personal components. It is substantiated that the basis of ensuring the competitiveness of the working population is its continuous support, development and protection. Originality. The competitiveness of the working population is seen as a mechanism of lifelong accumulation of competitiveness through the development of human capital as an opportunity to implement competitive advantage in the labour market in order to form material security, required level and quality of life and working lives. Practical value. The results of the research can be used for writing scientific papers in the direction of the studied problem: ensuring competitiveness in the labour market, competitiveness of the labour force, development of human capital.